Faktor-Faktor yang Berhubungan dengan Pemanfaatan Pelayanan Kesehatan pada Penderita Hipertensi di Puskesmas Oesao - Elisabet Nona Lince; Masrida Sinaga; Tasalina Yohana Parameswari Gustam; Fransiskus G. Mado (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
The utilization of health services for hypertension patients is important because hypertension is a deadly disease without any symptoms first. Regular blood pressure measurement at health care facilities is very important to maintain the development of the disease, prevent complications and reduce the risk of death due to hypertension. The purpose of this study was to determine the factors associated with the utilization of health services in hypertension patients at the Oesao Health Center. The research method used was cross-sectional research. The research sample consisted of 89 people selected by simple random sampling. Data analysis was univariate and bivariate analysis using the chi-square test. The results showed that variables that had a relationship with the utilization of health services in hypertension patients were, insurance ownership (p = 0.031), family support (p = 0.030), and perception of illness (p = 0.000). The variable that did not have a relationship with the utilization of health services in hypertension patients was accessibility (p = 0.679). So it can be concluded that there is a relationship between insurance ownership, family support, and perception of illness with the utilization of health services in hypertension patients at the Oesao Health Center.